AmphiNom: an amphibian systematics tool. Issue 1 (2nd January 2019) - Liedtke, H. Christoph
Abstract : Large-scale comparative and systematic studies rely on the seamless merging of multiple datasets. However, taxonomic nomenclature is constantly being revised making it problematic to combine data from different resources or different years of publication, which use different synonyms. This is certainly true for amphibians, which have experienced a spike in taxonomic revisions in part as the result of the widespread use of DNA barcoding to resolve cryptic species delimitation issues and large-scale collaborative efforts to revise the entire amphibian tree. The 'Amphibian Species of the World Online Reference' (ASW) is one of the most widely used and most regularly updated databases for amphibian taxonomy, but existing R tools for querying synonyms such as 'taxize' do not include this resource. 'AmphiNom' is a tool suite written in the R programming language designed to facilitate batch-querying amphibian species names against the ASW database. This facilitates the merging of datasets that use different nomenclature and its functionality is easily integrated into customizable R workflows. Moreover, it allows direct querying of the ASW website using R and straightforward reporting of summary information on current amphibian systematics.